PKM Pengembangan Metode Hitung Cepat Dengan Media Sempoa - Agus Sifaunajah; Khoirun Nisa; Ika Nur Amaliah; Durrotul Hikmah (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The development of a quick count method using abacus media in the Barongsawahan KKN learning guidance aims to develop student’s thinking skills and interest in mathematics. This activity is carried out for weeks, with a meeting duration of 60 minutes per meeting. Students who take part in the activities are student who are considered capale of participating in the training. Namely from six grade. The material taughtfirst is about the components on the abacus, then the basic abacus formulas are used. The abacus used is an abacus with five seeds or beads, one bead above and four beads below the diving line. Student response is very good in carrying out activities because the abacus is new to them, besides that by being taught the abacus students became more enthusiastic and focused on taking math lesson in the class.